Estimation of residual stress of metal material without plastic plateau by using continuous spherical indentation. (May 2019) - Wang, Zhanyu; Deng, Leixiong; Zhao, Jianping
Abstract: This paper presents a method to allow the measurement of residual stress ( σ r ), yield strength ( σ y ) and strain hardening exponent ( n ) of metal materials through continuous spherical indentation test. Based on the analysis of finite element simulation results, a new fitting equation between the indentation response parameter and the material properties was given in this paper. The influence of friction and the mesh size of finite element model was also discussed when the residual stress is included in the material. Only three load values are required at each different indentation depths, and the three unknown parameters ( σ r, σ y and n ) can be obtained through corresponding dimensionless functions based on the reverse analysis. Finally, the validation of the method presented in this paper was verified by simulating the material (SUS304) with the known material parameters in the literature. Results show that the method proposed in this paper can accurately predict the residual stress, yield strength and strain hardening exponent of metal materials from the indentation load-depth curve. Highlights: In this paper, a new dimensionless function l n P / ( σ y ⋅ h 2 ) = ∏ * ( E / σ y, n, σ r / σ y ) is given for material parameters and residual stresses. The effect of friction and size of element mesh on the model is negligible for a material with residual stress. A reverse analysis algorithm can be used to estimate the residual stress of metal material without plastic plateau.